Small-scale and Smartphone-based Colorimetric Experiments to Enhance Grade-11 Students’ Conceptual Understanding of Chemical Equilibrium - Wuttisela, Karntarat; Jarujamrus, Purim; Chairam, Sanoe; Supasorn, Saksri (Jurnal Pendidikan IPA Indonesia, 2024)
This study aimed to examine the conceptual understanding of chemical equilibrium among 11th-grade students using the 5E inquiry learning framework, in which the students were requested to conduct the small-scale experiments on chemical equilibrium and factors influencing the equilibrium and the smartphone-based colorimetric determination of Kc. Data collection was conducted through a two-tier diagnostic conceptual test and semi-structured interviews. Thirty-one students participated in three 2-hour 5E learning sessions, totaling 6 hours. A paired-samples t-test revealed that the post-conceptual test scores (mean 31.46, S.D. 6.82, 69.91%) were significantly higher than the pre-test scores (mean 11.85, S.D. 10.80, 26.33%) at a significance level of 0.05, with a normalized gain of 0.59, indicating a medium improvement. Most students progressed from the less accurate category, Partial Understanding with Specific Misunderstanding (PMU, 42.39%), to a more accurate category, Partial Understanding (45.38%). Semi-structured interviews suggested that the 5E inquiry approach, using small-scale and smartphone-based colorimetric experiments, was both engaging and effective in improving students’ conceptual understanding. This intervention successfully helped students shift their understanding of chemical reactions towards more accurate categories.